2013
DOI: 10.1016/j.pain.2013.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter structural properties predict transition to chronic pain

Abstract: Neural mechanisms mediating the transition from acute to chronic pain remain largely unknown. In a longitudinal brain imaging study, we followed patients with a single subacute back pain (SBP) episode for over one year as their pain subsided (SBPr), or persisted (SBPp) representing a transition to chronic pain. We discovered brain white-matter structural abnormalities (in n=24 SBP; SBPp=12 and SBPr=12), as measured by diffusion tensor imaging (DTI), at entry into the study in SBPp in comparison to SBPr. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
190
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 38 publications
10
190
1
1
Order By: Relevance
“…Future investigations of whether WS change as the result of central sensitisation 6,36 should use a longitudinal study design in which some participants may go on to develop chronic LBP from the sub-acute stage.…”
Section: Pain Anticipation In Chronic Low Back Pain 20mentioning
confidence: 99%
“…Future investigations of whether WS change as the result of central sensitisation 6,36 should use a longitudinal study design in which some participants may go on to develop chronic LBP from the sub-acute stage.…”
Section: Pain Anticipation In Chronic Low Back Pain 20mentioning
confidence: 99%
“…89 Functional MRI (fMRI) has shown that the default-mode network (DMN), a network of brain areas active in a resting, non-focused state, is disrupted after TBI. 90 Imaging studies have an advantage over animal models for study of PTH in that headache can be more directly targeted as a symptom.…”
Section: Physiology Of Post-traumatic Headachementioning
confidence: 99%
“…13 The role of diagnostic and treatment approaches focusing on peripheral "pain generators" are evolving as the evidence for central modulation of pain intensity in chronic musculoskeletal pain grows. 14,15 The analgesic benefit of duloxetine in recent clinical trials of nondepressed patients with axial predominant chronic low back pain bolsters the search for therapeutic targets in the CNS. 16 Treatments shown to address the psychosocial variables that often modulate chronic pain intensity, such as fear avoidance and catastrophizing, are an essential concomitant of medical and procedural approaches.…”
mentioning
confidence: 99%